Can MachinesDo Art? Non human interventions in art and fashion - Thompson, Reynaldo; Mukhopadhyay, Tirtha (DAT Journal, 2021)
The first step in the evolution of technologically driven visual art genres was taken with the application of controlling spray guns and electrical brushes by David Alvaro Siqueiros 1920. The decisive break occurs again in contemporary fashion designs and installations (Savage Beauty 2011). Hence we have to emphasize upon the growing insularity and autonomy of technologically rebellious art – in the reduced human intention in patterns on dresses exhibited by the fashion maverick Alexander McQueen. We shall be able to appreciate the fact that the form of representation is most likely to be similar to a mechanics of accidence and autonomy, rather than control, and reflective of the independence of the machine itself, now called the machine being.